2018
DOI: 10.3390/ijerph15081697
|View full text |Cite
|
Sign up to set email alerts
|

Sanger and Next Generation Sequencing Approaches to Evaluate HIV-1 Virus in Blood Compartments

Abstract: The implementation of antiretroviral treatment combined with the monitoring of drug resistance mutations improves the quality of life of HIV-1 positive patients. The drug resistance mutation patterns and viral genotypes are currently analyzed by DNA sequencing of the virus in the plasma of patients. However, the virus compartmentalizes, and different T cell subsets may harbor distinct viral subsets. In this study, we compared the patterns of HIV distribution in cell-free (blood plasma) and cell-associated viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 52 publications
(55 reference statements)
4
21
0
Order By: Relevance
“…Although Sanger automated sequencing is generally limited to the detection of variants with greater than 20% of prevalence [16], the two RASs mentioned above could not be detected by automated sequencing. This lack of correlation between both sequencing methods was probably due to the fact that both samples exhibited low viral loads (3.2 log 10 copies/mL), as it was previously reported [61]. In fact, it has been estimated that the efficiency of RNA extraction and cDNA synthesis is 1% to 10% [62]; thus, in low viral load samples, the small number of molecules present in the cDNA could be better examined by the higher analytical sensitivity of NGS [63].…”
Section: Discussionmentioning
confidence: 72%
“…Although Sanger automated sequencing is generally limited to the detection of variants with greater than 20% of prevalence [16], the two RASs mentioned above could not be detected by automated sequencing. This lack of correlation between both sequencing methods was probably due to the fact that both samples exhibited low viral loads (3.2 log 10 copies/mL), as it was previously reported [61]. In fact, it has been estimated that the efficiency of RNA extraction and cDNA synthesis is 1% to 10% [62]; thus, in low viral load samples, the small number of molecules present in the cDNA could be better examined by the higher analytical sensitivity of NGS [63].…”
Section: Discussionmentioning
confidence: 72%
“…Arias et al also found strong agreement with MiSeq-generated HIV-1 NGS data analyzed by HyDRA Web software using a 20% frequency cutoff to that using Sanger-based sequencing; additional DRMs were seen from the NGS data when using a 5% frequency cutoff [19]. In addition, Tzou et al reported a strong correlation between data generated using Sanger sequencing and that from an in vitro diagnostic NGS assay [20].…”
Section: Discussionmentioning
confidence: 87%
“…Both Sanger and NGS are accurate, though some studies have disagreed on which is more accurate for the detection of low frequency mutations (e.g., Ihle et al, 2014;Arsenic et al, 2015;Beck et al, 2016). Most of the studies comparing sequences derived from the two methods show a high correlation between the two methodologies (Gunnarsdottir et al, 2011;Arsenic et al, 2015;Arias et al, 2018). Critically, all of these studies have been focused on clinical research using fresh samples (e.g., blood, organ tissues, etc.)…”
Section: Sanger Sequencing and Next-generationmentioning
confidence: 99%